DAUN SALAM DALAM MENINGKATKAN KEMANDIRIAN DAN KESEJAHTERAAN EKONOMI BAGI WARGA DUSUN LOSARI KEC. GUDO KAB. JOMBANG - Pambudi, Rizky Kurniawan (J-Mabes: Jurnal Manajemen, Akuntansi, Bisnis dan Studi Ekonomi Syariah, 2024)
Independence shows confidence in one's own ability to solve problems without help from others. Welfare is defined as a condition where a person or group of people, men and women are able to fulfill their basic rights to maintain and develop a dignified life. The residents of Losari hamlet try to achieve independence and economic prosperity through the bay leaf pricking business. Where before implementing the bay leaf pricking business there was no balance in income and expenses. This research method is qualitative where the data source consists of primary data, namely the head of RT 01 and residents of Losari hamlet. Secondary data consists of financial records and payment receipts. From the results of the research and analysis that has been carried out, it is known that the residents of Losari Hamlet can be said to be independent and prosperous after implementing the bay leaf pricking business. These results were obtained from the fulfillment of all indicators of independence and prosperity after implementing the bay leaf pricking business.